Raden Syarif Abdullah Assegaff: His Role in the Arab Rebellion in Palembang and His Exile to Minahasa - Kembuan, Roger Allan Christian; Kaunang, Ivan Robert Bernadus (Potret Pemikiran, 2023)
The emergence of a small Arab community in the interior of Minahasa during the colonial period began with the arrival of an important figure named Raden Syarif Abdullah Assegaf who was involved in an event known as the Arab Revolt in Palembang in 1881. The purpose of this research is to reveal the role of Raden Syarif Abdullah Assegaf in the 1881 Arab uprising in Palembang and his exile in Tondano, Minahasa. This research uses several data sources from the colonial period, travel reports, and interviews with Arab descendants living in Minahasa. This research uses the critical historical method to conduct phased research and detailed analysis. The results of this study are the role of an Arab descent figure named Raden Syarif Abdullah Assegaf in the Arab uprising in Palembang in 1881 as the leader of the rebellion movement, from the event then he was exiled to Minahasa along with his family by the colonial government and when he was in exile Tondano, became a religious leader for the Jaton community by bringing some changes such as Hadrah; and from the aspect of family relations from marriage in Minahasa gave birth to several figures who were quite important in the propagation of Islam in North Sulawesi.